Cytoplasmic cyclin D1 regulates cell invasion and metastasis through the phosphorylation of paxillin - Noel P. Fusté (Nature Portfolio, 2016)
Previous studies suggest that Cyclin D1 may regulate cell adhesion and migration but the mechanisms underlying such regulation and the relevance to cancer development are unknown. Here, Fusté et al. show that Cyclin D1/Cdk4 phosphorylates paxillin and thereby promotes cellular migration and metastasis.